Fixed Drug Eruption: Case Report - Azhari Gani; Muhammad Jailani (Britain International for Academic Research (BIAR) Publisher, 2020)
Drug allergy is characterized by hypersensitivity reactions to pharmacological agents, having an immune mechanism of development. In these reactions antibody and/or activated T cells are directed against medications or their metabolites. This problem is rather urgent for practical healthcare, as over 7% of people suffer from drug allergy. A 54-year old male presented at the emergency room Hospital Zainoel Abidin with redness and swelling of the bodies of a burning sensation, itching pain. In the detailed anamnesis taken from the patient, it was learned that 1 days previously he had consulted a nurse with the fever and 60 min after examination had been prescribed with acid mefenamic. Hypersensitivity immune reactions to medications, according to the present concepts, are divided into immediate reactions (within 1–6 h after starting the preparation manifesting with various forms—from mild to life-threatening symptoms of anaphylaxia), or delayed reactions (several hours to several days after the offending medication is started, manifesting clinically with exanthemas in the majority of cases). Drug allergy should be prevented.Steps to prevent allergic drug reactions include (1) a careful history to determine host risk factors, (2) avoidance of cross-reactive drugs, (3) use of predictive tests when available, (4) proper and prudent prescribing of drugs (especiallyantibiotics) that are frequently associated with adverse reactions,(5) use of oral drugs when possible, and (6) documentation of drug allergy in the patient’s medical record.